A low-zinc environmentally friendly rubber composition and preparation method thereof

By combining butadiene rubber with polystyrene butadiene rubber and optimizing the dispersion and interface of filler, a low-zinc environmentally friendly rubber composition is prepared, which solves the problems of existing transparent rubber wear, aging and environmental pollution, and achieves the effect of efficient vulcanization and excellent performance.

CN119735869APending Publication Date: 2025-04-01PUYANG COSMOS CHEM CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411927129.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing transparent rubber compositions are prone to wear and aging during use, and the zinc-containing active agents have a risk of environmental pollution, making it difficult to meet environmental protection and performance requirements.

Method used

By innovatively combining butadiene rubber with polystyrene butadiene rubber, the dispersion and interface combination of white carbon black, white oil and modified silane coupling agent is optimized, and low-zinc active agent and vulcanizing agent are combined to synergize the vulcanization reaction to prepare a low-zinc environmentally friendly rubber composition.

Benefits of technology

It achieves efficient vulcanization and excellent performance of rubber, improves transparency and comprehensive performance, reduces the use of zinc, and meets the needs of green development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005209501010000031
    Figure BDA0005209501010000031
  • Figure BDA0005209501010000091
    Figure BDA0005209501010000091
  • Figure BDA0005209501010000101
    Figure BDA0005209501010000101
Patent Text Reader

Abstract

The present invention belongs to the field of rubber technology, and in particular to a low-zinc environment-friendly rubber composition and a preparation method thereof. The rubber composition includes the following components in parts by weight: 65-75 parts of cis-butadiene rubber, 25-35 parts of solution-polymerized styrene-butadiene rubber, 40-45 parts of white carbon black, 12-16 parts of white oil, 1-3 parts of modified silane coupling agent, 1-2 parts of activator, 1.3-1.7 parts of vulcanizing agent, 1.5-2.5 parts of dialkyl dithiophosphate zinc, 0.5-1 parts of dibenzothiazole disulfide; The present invention sequentially prepares a modified silane coupling agent by an epoxy ring-opening reaction and an esterification reaction, and introduces benzothiazole and phosphate ester into the molecular structure of the silane coupling agent. The rubber composition prepared by the present invention maintains a good light transmittance, and also has excellent wear resistance, flame retardancy, mechanical properties and anti-aging properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rubber, and in particular relates to a low-zinc environmentally friendly rubber composition and a preparation method thereof. Background Art

[0002] In the field of modern materials science, transparent rubber plays a key role in many industries with its unique optical properties and practical characteristics, and has broad application prospects in fields ranging from food packaging, medical supplies to optical devices. However, its research and development and production face many technical difficulties and challenges. Raw material selection and vulcanization system construction are the core factors that determine the performance and environmental friendliness of transparent rubber.

[0003] In the selection of transparent rubber raw materials, there are various types of raw rubber, each with its own characteristics. The molecular chain saturation of ethylene-propylene rubber (EPR) is high, which gives the rubber excellent aging resistance and chemical corrosion resistance. Its regular molecular structure is conducive to light transmission, laying the foundation for the transparency of rubber products; natural rubber has a wide range of sources, good processing performance and excellent elasticity, and has both flexibility and transparency; the high cis structure of butadiene rubber gives it low-temperature compliance and high elasticity, which is of great significance to improving the dynamic performance of rubber; styrene-butadiene rubber has both characteristics through the copolymerization of styrene and butadiene, and can optimize transparency and comprehensive performance through molecular design. The selection of fillers should not be ignored. Basic magnesium carbonate has great application potential due to its own crystal structure and optical properties, but in actual production, purity fluctuations become a limiting factor. When the purity is not enough, impurities will interfere with the light propagation path, resulting in reduced rubber transparency, and its interaction with rubber molecules is weak, and it cannot effectively enhance the rubber network structure, and the reinforcement effect needs to be improved. In contrast, silica has a nanoscale spherical or chain structure. Its high specific surface area and unique surface activity give it strong adsorption properties. It is tightly combined with rubber molecules to form a stable three-dimensional network, which can significantly improve the mechanical properties of rubber products. At the same time, its own optical uniformity and low refractive index further ensure the high transparency of rubber products.

[0004] The construction of the vulcanization system is also a bottleneck in transparent rubber technology. Peroxide vulcanization uses a free radical reaction mechanism to achieve rubber cross-linking. No heteroatoms or chromophores are introduced during the process, ensuring the purity and transparency of the rubber. However, this method destroys the flexibility and regularity of the rubber molecular chain and weakens the intermolecular forces, causing the key mechanical properties of rubber products, such as tear strength and elastic modulus, to decline. In addition, the reaction is rapid, the scorch time is short, the processing window is narrow, and early vulcanization is prone to occur during production, resulting in a high scrap rate, which limits its large-scale application. Sulfur vulcanization relies on a complex chemical process to build a stable cross-linked network through polysulfide bonds, giving rubber products excellent comprehensive properties. The extended scorch time can improve processing safety and flexibility, and is widely used in the manufacture of multiple products. However, when using sulfur vulcanization, it is generally necessary to use zinc-containing activators such as zinc oxide to promote activation.

[0005] With the development and progress of society, people pay more and more attention to environmental protection, and their environmental awareness is gradually increasing. The bioaccumulative toxicity of zinc has attracted attention. When zinc is released into water, it will interfere with microbial metabolism, destroy the physiological functions of aquatic organisms, and endanger the ecological balance. In addition, the existing rubber compositions are often prone to wear during use due to the insufficient bonding between the rubber matrix and the filler, or the unreasonable type and amount of filler. In use, they are also affected by various factors, aging occurs, and physical properties are reduced, all of which affect the life and reliability of rubber products; in addition, the rubber composition itself is usually flammable, which limits its application in some special fields. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a low-zinc environmentally friendly rubber composition and a preparation method thereof. By innovatively combining cis-1,4-butadiene rubber and solution-polymerized styrene-butadiene rubber, the advantages of the two are complementary, white carbon black, white oil, and modified silane coupling agent are accurately formulated, filler dispersion and the interface bonding between rubber and filler are optimized, and then an activator, a vulcanizing agent, dialkyl dithiophosphate zinc, and dibenzothiazole disulfide are compounded to synergistically activate the vulcanization reaction. This formulation process breaks through the limitations of traditional high zinc, opens up a new path to improve the transparency and comprehensive performance of rubber under low zinc conditions, meets the needs of green development, and greatly expands the application scope of transparent rubber products.

[0007] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:

[0008] A low-zinc environmentally friendly rubber composition, comprising the following components in parts by weight: 65-75 parts of butadiene rubber, 25-35 parts of solution-polymerized styrene-butadiene rubber, 40-45 parts of white carbon black, 12-16 parts of white oil, 1-3 parts of modified silane coupling agent, 1-2 parts of activator, 1.3-1.7 parts of vulcanizing agent, 1.5-2.5 parts of zinc dialkyl dithiophosphate, and 0.5-1 part of dibenzothiazole disulfide;

[0009] The preparation method of the modified silane coupling agent is as follows:

[0010] Step S1, raising the temperature of N,N-dimethylformamide to 100-110° C. under stirring, then sequentially adding benzothiazole-6-acetic acid, 5,6-epoxyhexyltriethoxysilane, and chromium acetate, reacting for 5-7 hours, cooling to room temperature, and obtaining an intermediate after purification;

[0011] Step S2, dispersing the intermediate obtained in step S1 in acetone under stirring, raising the temperature to 50-60° C., then adding phosphoric acid, reacting for 6-8 hours, cooling to room temperature, and obtaining a modified silane coupling agent after purification;

[0012] The synthetic route of modified silane coupling agent is as follows:

[0013]

[0014] The invention uses benzothiazole-6-acetic acid and 5,6-epoxyhexyltriethoxysilane as starting materials, and carries out a ring-opening reaction of epoxy compounds under the catalysis of chromium acetate to obtain an intermediate; then uses the intermediate and phosphoric acid as raw materials, and carries out an esterification reaction under heating conditions to obtain a modified silane coupling agent.

[0015] In order to obtain a silane coupling agent and ensure product consistency, the molar ratio of benzothiazole-6-acetic acid, 5,6-epoxyhexyltriethoxysilane, and chromium acetate in step S1 is 1.1:0.9-1.0:0.01-0.02, and the amount of benzothiazole-6-acetic acid added to the N,N-dimethylformamide is 0.1-0.2 g / mL; the molar ratio of the intermediate and phosphoric acid in step S2 is 1:1.1-1.3, and the amount of the intermediate added to the acetone is 0.13-0.16 g / mL.

[0016] Furthermore, the vulcanizing agent is sulfur, and the activating agent is zinc oxide.

[0017] The present invention also provides a method for preparing a low-zinc environmentally friendly rubber composition, comprising the following steps: adding cis-1,4-butadiene rubber and solution-polymerized styrene-butadiene rubber into an internal mixer, performing internal mixing at a first preset temperature, and then sequentially adding white carbon black, white oil, modified silane coupling agent, activator, vulcanizing agent, zinc dialkyl dithiophosphate, and dibenzothiazole disulfide, performing internal mixing at a second preset temperature, and performing vulcanization to obtain the composition.

[0018] Furthermore, the first preset temperature is 120-140°C, and the banburying time at the first preset temperature is 5-15 minutes; the second preset temperature is 70-90°C, and the banburying time at the second preset temperature is 20-40 minutes; the vulcanization temperature is 140-160°C, and the vulcanization time is 10-20 minutes.

[0019] The present invention has the following beneficial effects:

[0020] The present invention sequentially prepares a modified silane coupling agent through an epoxy compound ring-opening reaction and an esterification reaction, and introduces benzothiazole and phosphate into the molecular structure of the silane coupling agent. Benzothiazole can form a stable cross-linking structure by participating in the vulcanization reaction of rubber. This cross-linking structure enhances the interaction force between rubber molecular chains, which can not only resist the erosion of the composition by the external environment, but also improve the mechanical properties of the composition; Benzothiazole has a large steric hindrance, which can give the silane coupling agent good dispersibility, prevent direct contact and agglomeration between filler particles, refine the agglomerates of the filler, and improve the hydrophilicity of the filler surface, increase the compatibility of the filler with non-polar rubber, and thus help reduce the wear of the rubber during the friction process and improve the wear resistance of the composition. Phosphate can synergize with nitrogen and silicon elements in the modified silane coupling agent, and significantly improve the flame retardant properties of the compound through the flame retardant effect of the gas phase and the condensed phase, the enhancement of the carbon layer, the reduction of the heat release, and the like, thereby improving the flame retardant properties of the composition.

[0021] The present invention combines cis-1,4-butadiene rubber and solution-polymerized styrene-butadiene rubber, and the two are synergistic and complementary. By compounding white carbon black, white oil, and modified silane coupling agent, dispersion and interface bonding are optimized, and then compounding with an activator, a vulcanizing agent, zinc dialkyl dithiophosphate, and dibenzothiazole disulfide, synergistic activation and vulcanization are performed to obtain a rubber composition with a stable cross-linked structure. The present invention achieves efficient vulcanization and excellent performance of rubber without using a large amount of zinc-containing compounds through an innovative formula and vulcanization system, and provides a new idea and method for the sustainable development of the rubber industry. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0023] Butadiene rubber, model BR9000, active ingredient content 99%, brand Xinyuhong; solution polystyrene butadiene rubber, model SSBRT2003, brand Shanghai Gaoqiao; white carbon black, model AEROSIL 200, mesh number 200, brand Zhongbei Chemical; white oil, specific gravity 0.85, flash point 196℃, pour point -45℃, brand Haochen; zinc oxide, particle size 50-300nm, active ingredient content 99.99%, brand Ruihuang Metal; sulfur, purity 99.99%, mesh number 600. The raw materials used in the following examples are all common commercial products.

[0024] Example 1

[0025] A low-zinc environmentally friendly rubber composition comprises the following components in parts by weight: 70 parts of butadiene rubber, 30 parts of solution-polymerized styrene-butadiene rubber, 42 parts of white carbon black, 14 parts of white oil, 2 parts of modified silane coupling agent, 1.5 parts of activator, 1.5 parts of vulcanizer, 2 parts of zinc dialkyl dithiophosphate, and 0.8 parts of dibenzothiazole disulfide; wherein the vulcanizer is sulfur and the activator is zinc oxide;

[0026] The preparation method of the modified silane coupling agent is:

[0027] Step S1, under the stirring condition of 180rpm, the temperature of N,N-dimethylformamide is raised to 105°C, and then benzothiazole-6-acetic acid, 5.6-epoxyhexyltriethoxysilane, and chromium acetate are added in sequence, reacted for 6h, naturally cooled to room temperature, and then deionized water and ethyl acetate are added for extraction (the volume ratio of N,N-dimethylformamide, deionized water and ethyl acetate is 1:1:2), and the organic phase is distilled under reduced pressure and vacuum dried at 60°C for 12h to obtain an intermediate; wherein the molar ratio of the benzothiazole-6-acetic acid, 5.6-epoxyhexyltriethoxysilane and chromium acetate is 1.1:0.95:0.015, and the amount of benzothiazole-6-acetic acid added to the N,N-dimethylformamide is 0.15g / mL;

[0028] Step S2, under stirring at 180 rpm, dispersing the intermediate obtained in step S1 in acetone, raising the temperature to 55° C., then adding phosphoric acid, reacting for 7 hours, naturally cooling to room temperature, removing part of the acetone after concentration, and then extracting with ethyl acetate (the volume ratio of ethyl acetate to acetone before concentration is 1:1), taking the ester phase under reduced pressure distillation, and vacuum drying at 60° C. for 24 hours to obtain a modified silane coupling agent; wherein the molar ratio of the intermediate to phosphoric acid is 1:1.2, and the amount of the intermediate added to the acetone is 0.14 g / mL;

[0029] The NMR results of the modified silane coupling agent are: 1 H NMR (300MHz, DMSO-d6) δ9.23 (s, 1H), 8.05 (d, 1H), 7.93 (d, 1H), 7.60 (d, 1H), 4.50-4.54 (m, 1H), 4.21-5.25 (m , 3H), 4.06-4.09(m, 1H), 3.81-3.83(m, 6H), 3.70(s, 2H), 1.55-1.59(m, 2H), 1.21-1.25(m, 13H), 0.56(t, 2H).

[0030] A method for preparing a low-zinc environment-friendly rubber composition comprises the following steps: adding cis-1,4-butadiene rubber and solution-polymerized styrene-butadiene rubber into an internal mixer at a rotation speed of 50 revolutions per minute, internal mixing for 10 minutes at a first preset temperature of 130°C, and naturally allowing to stand for 12 hours after the internal mixing is completed; then sequentially adding white carbon black, white oil, modified silane coupling agent, activator, vulcanizing agent, zinc dialkyl dithiophosphate, and dibenzothiazole disulfide, internal mixing for 30 minutes at a second preset temperature of 80°C, and naturally allowing to stand for 12 hours after the internal mixing is completed; and finally vulcanizing at a temperature of 150°C for 15 minutes using a flat vulcanizer, and naturally cooling to room temperature to obtain the composition.

[0031] Example 2

[0032] A low-zinc environmentally friendly rubber composition comprises the following components in parts by weight: 65 parts of butadiene rubber, 35 parts of solution-polymerized styrene-butadiene rubber, 40 parts of white carbon black, 12 parts of white oil, 3 parts of modified silane coupling agent, 2 parts of activator, 1.3 parts of vulcanizer, 1.5 parts of zinc dialkyl dithiophosphate, and 0.5 parts of dibenzothiazole disulfide; wherein the vulcanizer is sulfur and the activator is zinc oxide;

[0033] The preparation method of the modified silane coupling agent is:

[0034] Step S1, under the stirring condition of 180rpm, the temperature of N,N-dimethylformamide is raised to 100°C, and then benzothiazole-6-acetic acid, 5.6-epoxyhexyltriethoxysilane, and chromium acetate are added in sequence, reacted for 7h, naturally cooled to room temperature, and then deionized water and ethyl acetate are added for extraction (the volume ratio of N,N-dimethylformamide, deionized water and ethyl acetate is 1:1:2), and the organic phase is distilled under reduced pressure and vacuum dried at 60°C for 12h to obtain an intermediate; wherein the molar ratio of the benzothiazole-6-acetic acid, 5.6-epoxyhexyltriethoxysilane and chromium acetate is 1.1:0.9:0.01, and the amount of benzothiazole-6-acetic acid added to the N,N-dimethylformamide is 0.2g / mL;

[0035] Step S2, under stirring at 180 rpm, dispersing the intermediate obtained in step S1 in acetone, raising the temperature to 50° C., then adding phosphoric acid, reacting for 8 hours, naturally cooling to room temperature, removing part of the acetone after concentration, and then extracting with ethyl acetate (the volume ratio of ethyl acetate to acetone before concentration is 1:1), taking the ester phase under reduced pressure distillation, and vacuum drying at 60° C. for 24 hours to obtain a modified silane coupling agent; wherein the molar ratio of the intermediate to phosphoric acid is 1:1.1, and the amount of the intermediate added to the acetone is 0.13 g / mL.

[0036] A method for preparing a low-zinc environment-friendly rubber composition comprises the following steps: adding cis-1,4-butadiene rubber and solution-polymerized styrene-butadiene rubber into an internal mixer at a rotation speed of 50 revolutions per minute, internal mixing for 15 minutes at a first preset temperature of 120°C, and naturally allowing to stand for 12 hours after the internal mixing is completed; then sequentially adding white carbon black, white oil, modified silane coupling agent, activator, vulcanizing agent, zinc dialkyl dithiophosphate, and dibenzothiazole disulfide, internal mixing for 40 minutes at a second preset temperature of 70°C, and naturally allowing to stand for 12 hours after the internal mixing is completed; and finally vulcanizing at a temperature of 140°C for 20 minutes using a flat vulcanizer, and naturally cooling to room temperature to obtain the composition.

[0037] Example 3

[0038] A low-zinc environmentally friendly rubber composition, comprising the following components in parts by weight: 75 parts of butadiene rubber, 25 parts of solution-polymerized styrene-butadiene rubber, 45 parts of white carbon black, 16 parts of white oil, 1 part of modified silane coupling agent, 1 part of activator, 1.7 parts of vulcanizer, 2.5 parts of zinc dialkyl dithiophosphate, and 1 part of dibenzothiazole disulfide; wherein the vulcanizer is sulfur and the activator is zinc oxide;

[0039] The preparation method of the modified silane coupling agent is:

[0040] Step S1, under the stirring condition of 180rpm, the temperature of N,N-dimethylformamide is raised to 110°C, and then benzothiazole-6-acetic acid, 5.6-epoxyhexyltriethoxysilane, and chromium acetate are added in sequence, reacted for 5h, naturally cooled to room temperature, and then deionized water and ethyl acetate are added for extraction (the volume ratio of N,N-dimethylformamide, deionized water and ethyl acetate is 1:1:2), and the organic phase is distilled under reduced pressure and vacuum dried at 60°C for 12h to obtain an intermediate; wherein the molar ratio of the benzothiazole-6-acetic acid, 5.6-epoxyhexyltriethoxysilane and chromium acetate is 1.1:1:0.02, and the amount of benzothiazole-6-acetic acid added to the N,N-dimethylformamide is 0.2g / mL;

[0041] Step S2, under stirring at 180 rpm, dispersing the intermediate obtained in step S1 in acetone, raising the temperature to 60° C., then adding phosphoric acid, reacting for 6 hours, naturally cooling to room temperature, removing part of the acetone after concentration, and then extracting with ethyl acetate (the volume ratio of ethyl acetate to acetone before concentration is 1:1), taking the ester phase under reduced pressure distillation, and vacuum drying at 60° C. for 24 hours to obtain a modified silane coupling agent; wherein the molar ratio of the intermediate to phosphoric acid is 1:1.3, and the amount of the intermediate added to the acetone is 0.16 g / mL.

[0042] A method for preparing a low-zinc environment-friendly rubber composition comprises the following steps: adding cis-1,4-butadiene rubber and solution-polymerized styrene-butadiene rubber into an internal mixer at a rotation speed of 50 revolutions per minute, internal mixing for 5 minutes at a first preset temperature of 140°C, and naturally allowing the mixture to stand for 12 hours after the internal mixing is completed; then sequentially adding white carbon black, white oil, modified silane coupling agent, activator, vulcanizing agent, zinc dialkyl dithiophosphate, and dibenzothiazole disulfide, internal mixing for 20 minutes at a second preset temperature of 90°C, and naturally allowing the mixture to stand for 12 hours after the internal mixing is completed; and finally vulcanizing at a temperature of 160°C for 10 minutes using a flat vulcanizer, and naturally cooling to room temperature to obtain the composition.

[0043] Example 4

[0044] A low-zinc environment-friendly rubber composition comprises the following components in parts by weight: 68 parts of butadiene rubber, 33 parts of solution-polymerized styrene-butadiene rubber, 44 parts of white carbon black, 15 parts of white oil, 2 parts of the modified silane coupling agent prepared in Example 1, 1 part of an activator, 1.4 parts of a vulcanizing agent, 2.2 parts of zinc dialkyl dithiophosphate, and 0.9 part of dibenzothiazole disulfide; wherein the vulcanizing agent is sulfur, and the activating agent is zinc oxide.

[0045] A method for preparing a low-zinc environment-friendly rubber composition comprises the following steps: adding cis-1,4-butadiene rubber and solution-polymerized styrene-butadiene rubber into an internal mixer at a rotation speed of 50 revolutions per minute, internal mixing for 7 minutes at a first preset temperature of 140°C, and naturally allowing the mixture to stand for 12 hours after the internal mixing is completed; then sequentially adding white carbon black, white oil, modified silane coupling agent, activator, vulcanizing agent, zinc dialkyl dithiophosphate, and dibenzothiazole disulfide, internal mixing for 25 minutes at a second preset temperature of 85°C, and naturally allowing the mixture to stand for 12 hours after the internal mixing is completed; and finally vulcanizing at a temperature of 145°C for 16 minutes using a flat vulcanizer, and naturally cooling to room temperature to obtain the composition.

[0046] Comparative Example 1

[0047] A low-zinc environmentally friendly rubber composition, comprising the following components in parts by weight: 72 parts of butadiene rubber, 33 parts of solution-polymerized styrene-butadiene rubber, 43 parts of white carbon black, 15 parts of white oil, 2 parts of modified silane coupling agent, 1.7 parts of activator, 1.5 parts of vulcanizer, 2 parts of zinc dialkyl dithiophosphate, and 0.6 parts of dibenzothiazole disulfide; wherein the vulcanizer is sulfur and the activator is zinc oxide;

[0048] The preparation method of the modified silane coupling agent is:

[0049] Under stirring at 180 rpm, the temperature of N,N-dimethylformamide was raised to 105°C, and then benzothiazole-6-acetic acid, 5.6-epoxyhexyltriethoxysilane and chromium acetate were added in sequence, the reaction was carried out for 6 hours, and the mixture was naturally cooled to room temperature. Deionized water and ethyl acetate were added for extraction (the volume ratio of N,N-dimethylformamide, deionized water and ethyl acetate was 1:1:2), and the organic phase was distilled under reduced pressure and dried in vacuo at 60°C for 12 hours to obtain the product; wherein the molar ratio of benzothiazole-6-acetic acid, 5.6-epoxyhexyltriethoxysilane and chromium acetate was 1.1:0.95:0.015, and the amount of benzothiazole-6-acetic acid added to the N,N-dimethylformamide was 0.15 g / mL.

[0050] A method for preparing a low-zinc environmentally friendly rubber composition is prepared according to the method described in Example 1.

[0051] Comparative Example 2

[0052] A low-zinc environmentally friendly rubber composition and a preparation method thereof are prepared according to the method described in Example 1, except that the modified silane coupling agent is replaced by 5,6-epoxyhexyltriethoxysilane.

[0053] The low-zinc environmentally friendly rubber compositions prepared in Examples 1-4 and Comparative Examples 1-2 were subjected to relevant tests. The tensile strength test and the elongation at break test were conducted in accordance with GB / T 1701-2001 "Determination of tensile strength and elongation at break of hard rubber", and the test conditions were: conventional (160°C, 15 min), aging (100°C, 4 d). The wear resistance test was conducted in accordance with GB / T9867-2008 "Determination of wear resistance of vulcanized rubber or thermoplastic rubber (rotating roller abrasion machine method)". The transmittance test was conducted in accordance with GB / T 2410-2008 "Determination of transmittance and haze of transparent plastics". The flame retardant performance test was carried out in accordance with ASTMUL94-2009. The sample with a size of 125mm×13mm×3mm was burned vertically. The vertical burning grade was: if the sample stopped burning within 10s and no molten droplets were generated, it was UL94-V0 grade; if the sample was extinguished within 30s of burning and no molten droplets were generated, it was UL94-V1 grade; if the sample was extinguished within 30s of burning and molten droplets were generated, it was UL94-V2 grade. The above tests were repeated three times to take the average value, and the test results are shown in Table 1. It can be seen from the data in Table 1 that compared with Comparative Examples 1-2, the low-zinc environmentally friendly rubber composition prepared in Examples 1-4 maintained a good light transmittance, and also had excellent wear resistance, flame retardancy and mechanical properties. After aging at 100°C and 4d, the low-zinc environmentally friendly rubber composition prepared in Examples 1-4 still maintained a tensile strength of more than 13.7MPa and a tensile elongation of more than 340%, showing good aging resistance. It can be seen from the data of Example 1 and Comparative Example 2 that the comprehensive performance of the rubber composition can be significantly improved by modifying the silane coupling agent and compounding the modified silane coupling agent with raw materials such as butadiene rubber, solution-polymerized styrene-butadiene rubber, white carbon black, a vulcanizing agent, and dibenzothiazole disulfide; it can be seen from the data of Comparative Examples 1-2 that the mechanical properties, wear resistance and flame retardancy of the rubber composition can be significantly improved by modifying the silane coupling agent in one step; and it can be seen from the data of Example 1 and Comparative Example 1 that the flame retardancy of the rubber composition can be further improved by modifying the silane coupling agent in two steps.

[0054] Table 1 Test results of relevant properties of low zinc environmentally friendly rubber composition

[0055]

[0056]

[0057] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A low-zinc environmentally friendly rubber composition, characterized in that: The invention comprises the following components in parts by weight: 65-75 parts of butadiene rubber, 25-35 parts of solution-polymerized styrene-butadiene rubber, 40-45 parts of white carbon black, 12-16 parts of white oil, 1-3 parts of modified silane coupling agent, 1-2 parts of activator, 1.3-1.7 parts of vulcanizing agent, 1.5-2.5 parts of zinc dialkyl dithiophosphate, and 0.5-1 parts of dibenzothiazole disulfide; The preparation method of the modified silane coupling agent is as follows: Step S1, under stirring conditions, raising the temperature of N,N-dimethylformamide to 100-110° C., then sequentially adding benzothiazole-6-acetic acid, 5,6-epoxyhexyltriethoxysilane, and chromium acetate, reacting for 5-7 hours, cooling to room temperature, and purifying to obtain an intermediate, the structural formula of the intermediate is: Step S2, under stirring conditions, dispersing the intermediate obtained in step S1 in acetone, raising the temperature to 50-60° C., then adding phosphoric acid, reacting for 6-8 hours, cooling to room temperature, and obtaining a modified silane coupling agent after purification. The structural formula of the modified silane coupling agent is:

2. The low-zinc environmentally friendly rubber composition according to claim 1, characterized in that: The molar ratio of benzothiazole-6-acetic acid, 5,6-epoxyhexyltriethoxysilane and chromium acetate in step S1 is 1.1:0.9-1.0:0.01-0.

02.

3. The low-zinc environmentally friendly rubber composition according to claim 2, characterized in that: The amount of benzothiazole-6-acetic acid added to the N,N-dimethylformamide is 0.1-0.2 g / mL.

4. The low-zinc environmentally friendly rubber composition according to claim 1, characterized in that: The molar ratio of the intermediate to phosphoric acid in step S2 is 1:1.1-1.

3.

5. The low-zinc environmentally friendly rubber composition according to claim 4, characterized in that: The amount of the intermediate added to the acetone is 0.13-0.16 g / mL.

6. The low-zinc environmentally friendly rubber composition according to claim 1, characterized in that: The vulcanizing agent is sulfur, and the activating agent is zinc oxide.

7. The method for preparing a low-zinc environment-friendly rubber composition according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: adding cis-1,4-butadiene rubber and solution-polymerized styrene-butadiene rubber into an internal mixer, performing internal mixing at a first preset temperature, then sequentially adding white carbon black, white oil, modified silane coupling agent, activator, vulcanizing agent, zinc dialkyl dithiophosphate and dibenzothiazole disulfide, performing internal mixing at a second preset temperature, and then performing vulcanization to obtain the product.

8. The method for preparing the low-zinc environment-friendly rubber composition according to claim 7, characterized in that: The first preset temperature is 120-140° C., and the banburying time at the first preset temperature is 5-15 minutes.

9. The method for preparing the low-zinc environment-friendly rubber composition according to claim 7, characterized in that: The second preset temperature is 70-90° C., and the banburying time at the second preset temperature is 20-40 min.

10. The method for preparing the low-zinc environment-friendly rubber composition according to claim 7, characterized in that: The vulcanization temperature is 140-160° C., and the vulcanization time is 10-20 minutes.